Development of a Design and Analysis Software of Co-rotating Twin-screw Gear Transmissions - Liu Guiyuan; Zhang Lei; Wei Peitang; Liu Genshen; Hu Mingzhu; He Zhiqiang; Liu Huaiju (Jixie chuandong)
For co-rotating twin-screw gear transmissions, due to the complexity of the design process, multiple parameters as well as model iterations, cumbersome process and manifold work are needed. It is essential to develop a design and analysis software to improve the designing effect and efficiency. In this work a design and optimization model for co-rotating twin-screw gear transmission is established to develop a professional design and analysis software. The software development is based on the C++ programing language and the Qt application framework. Combining engineering practice cases, the operability, effect of optimization, and reliability of the developed software have been verified. The results show that the mass of the gear transmission is reduced by 7.98% compared to engineering applications. Optimization results can achieve stable convergence with a convergence accuracy of 99.02%, and the gear safety factor can be controlled within 8%. The developed software is expected to promote the transformation and upgrading of industrial design methods.